1986
DOI: 10.1017/s0021859600069768
|View full text |Cite
|
Sign up to set email alerts
|

The nitrogen cycle in the Broadbalk Wheat Experiment: recovery and losses of 15N-labelled fertilizer applied in spring and inputs of nitrogen from the atmosphere

Abstract: SUMMARY15N-labelled nitrogen fertilizer (containing equal quantities of ammonium-N and nitrate-N) was applied in 4 consecutive years (1980–3) to different microplots located within the Broadbalk Wheat Experiment at Rothamsted, an experiment which has carried winter wheat continuously since 1843. Plots receiving 48, 96, 144 and 192 kg N/ha every year were given labelled fertilizer in mid-April at (nominally) these rates.Grain yields ranged from 1–2 t/ha on plots given no N fertilizer since 1843 to a maximum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(85 citation statements)
references
References 22 publications
5
79
0
1
Order By: Relevance
“…Where previous additions of manure had been made, N released from that source by mineralization may have substituted for fertilizer N. Similar observations have been made in previous studies (Powlson et al, 1986), As can be observed from Table 3, considerable amounts of mineral N remained in the 0-1.2 m zone at the end of the maize experiment in 1990. The decrease in mineral N contents on the zero N plots of the maize experiment was smaller than the total uptake of N by the crops.…”
Section: Discussionsupporting
confidence: 83%
“…Where previous additions of manure had been made, N released from that source by mineralization may have substituted for fertilizer N. Similar observations have been made in previous studies (Powlson et al, 1986), As can be observed from Table 3, considerable amounts of mineral N remained in the 0-1.2 m zone at the end of the maize experiment in 1990. The decrease in mineral N contents on the zero N plots of the maize experiment was smaller than the total uptake of N by the crops.…”
Section: Discussionsupporting
confidence: 83%
“…However, measurements were made in three experiments (Little Hoos 1983, Rotation I1 1982and Stackyard I 1982 and there (1'NH4)2S04 was less than 0.5 kg ha-' of fertiliserderived inorganic N in the 23-70cm layer. Previous work (Powlson et al 1986b) showed that even the total quantity of fertiliserderived N in soil below the plough layer was small, between 2 and 5 o/, of that applied. It is noteworthy that the soil containing the most labelled inorganic N at harvest was in a plot of the Broadbalk Wheat Experiment given no P or K fertiliser since 1843 (Table 3).…”
Section: Wheat Grown On Old Arable Landmentioning
confidence: 96%
“…The straw is removed at harvest in this section, and we assume residue incorporation of 38% of total above-ground residue (consisting of stubble and chaff and uncollected straw) for the control treatment, and 30% for the other fertilized treatments in this continuous wheat section as suggested by previous literature (Powlson et al 1986). For more details of the site and the treatments see http://www.era.rothamsted.ac.uk/ Broadbalk.…”
Section: Site Descriptionmentioning
confidence: 99%